Prevalence of asymptomatic bacteriuria among antenatal women and its effects on maternal and perinatal outcome in northern Andhra Pradesh population - V., Prabhavathi; B., Krishnamma; G., Krishna Murthy; DKV, Prasad (International Journal of Advances in Medicine, 2018)
Background: The pregnant women are more commonly affected with asymptomatic bacteriuria (ASB) than non-pregnant women and its progression could lead to adverse maternal and perinatal outcomes. The study was designed with an aim to know the prevalence of ASB and its effects on maternal and perinatal outcome. Methods: In this prospective study, 300 antenatal women attending Anil Neerukonda Hospital were screened for ASB. Urine culture was performed using standardized Kirby-Bauer disc diffusion method on blood agar, Mac Conkey’s agar for antibiotic sensitivity testing. The screened antenatal women were divided into two subgroups viz. asymptomatic bacteriuria positive (Group I) and asymptomatic bacteriuria negative (Group II) depending on the culture study and were followed till delivery for maternal and perinatal outcomes. Results: The prevalence of ASB was 11.33%. Out of 34 cases of ASB positive, 8 cases (23.5%) were delivered with birth weight <2500 grams as compared to 11 cases (4.1%) in unexposed cases (RR 5.68, 95% CI; 2.46-13.15; p<0.05). Preterm low birth was noticed in 5 (14.7%) cases of ASB positive pregnant women with compared to unexposed cases (RR 1.5, 95% CI; 0.61-3.65, p=0.36). Regarding maternal outcomes, premature labour was observed in 8 cases (23.5%) of ASB exposed women whereas 22 (8.3%) in non-exposed cases (RR 2.84, 95% CI; 1.37-5.88, p=0.004). A significant number of women have developed hypertension (17.6%) and preeclampsia (8.8%) in ASB positive cases as compared to ASB negative cases (4.9% and 2.3% respectively). Conclusions: The prevalence of ASB was 11.33% in the present study. As one third of the cases were identified in early and late trimesters, regular and trimester wise screening need to be incorporated in routine antenatal screening for safe motherhood and new born health.